302 Creating safer road designs: star ratings for road safety audits. (20th November 2022) - Smith, Greg; Beer, Kenn; Rogers, Luke
Abstract : Context: Road traffic crashes cause nearly 1.3 million preventable deaths and an estimated 50 million injuries each year. The Global Plan for the Decade of Action for Road Safety 2021–2030 sets a target reducing road deaths and injuries by 50% by 2030. One of the key recommendations of the Global Plan is that all road designs be subject to Road Safety Audits (RSA) to ensure they meet a minimum standard of three stars or better for all road users. Process: Road Safety Audits (RSA) and the iRAP Star Rating methodology have the same overall objective: to reduce road trauma, yet the two approaches are different. RSA are a formal, systematic and detailed examination of road safety concerns by an independent and qualified team of auditors. RSA leverage the knowledge and experience of these auditors and only present issues the auditors believe present risks to the travelling public. The iRAP methodology is a highly standardized, data and evidence driven process that produces quantifiable safety metrics such as star ratings and investment plans. As part of the Central Asia Regional Economic Cooperation (CAREC) program and with support of the Asian Development Bank (ADB), a Star Rating for Road Safety Audits manual has been developed to provide guidance on how RSA and the iRAP methodology may be combined to support implementation of the Global Plan. Outcomes: The manual presents practical ways that RSA and the iRAP methodology can be used together to harnesses the expert experience and independence of road safety auditors, while framing each audit finding within a data and evidence-driven global standard. The novel approaches developed in the manual may be applied to designs for new roads, road upgrades and road rehabilitation projects. Although the manual focuses on the CAREC region, it has practical applications globally.